When and why to treat the child who snores? - Tan, Hui-Leng; Alonso Alvarez, Maria Luz; Tsaoussoglou, Marina; Weber, Silke [UNESP]; Kaditis, Athanasios G. (Wiley, 2017)
Obstructive sleep-disordered breathing (SDB) can result in cardiovascular and neurocognitive morbidity as well as adversely affect behavior, growth, quality of life, and nocturnal continence. This article summarizes the latest evidence regarding the morbidity related to obstructive SDB, commenting on the impact of severity of obstruction, that is, the difference in effects seen of moderate to severe obstructive sleep apnea syndrome (OSAS) compared to those of mild OSAS or primary snoring. The impact of therapy is discussed, focusing on which children are likely to benefit from treatment interventions; namely those with moderate or severe OSAS irrespective of the presence of morbidity, children with mild OSAS with associated morbidity or predictors of SDB persistence such as obesity, and children with complex conditions accompanied by upper airway obstruction like craniosynostosis and Prader–Willi syndrome. The co-existing conditions which may improve when treatment for obstructive SDB is offered are reviewed, while the clinical parameters associated with spontaneous improvement or resolution of obstructive SDB are discussed. The intention being to enable clinicians to make informed decisions on who should be treated, when and why. Pediatr Pulmonol. 2017;52:399–412. © 2016 Wiley Periodicals, Inc.
Keywords: adenotonsillectomy; obesity; primary snoring